Ответы и объяснения

2013-06-25T21:40:05+00:00

а) у"=х^2-x-6

b)(3x-3-3x-4)/(x-1)^2=-7/(x-1)^2

c)(7x-5)(5x-64)+5(5x-7x^2)=35x^2-448-25x-320+25x-35x^2=-768

  • AlbuRin
  • светило науки
2013-06-26T03:44:04+00:00

a)       (X^3/3 -X^2/2 -6x) '  =  3*x^(3-1) /3 - 2*x^(2-1) /2 - 6 = x^2 - x -6

 

b)        ((3x+4)/(x-1)) '  =  ((3x+4) " * (x-1)  -  (3x+4)*(x-1) ")/(x-1)^2  =  (3*(x-1)  -  (3x+4)*1)/(x-1)^2  =

            =(3x - 3 - 3x  - 4)/(x-1)^2  =   -7/(x-1)^2

 

c)         ((5x-7x^2)(5x-64)) "    =  (5x-7x^2) "(5x-64)   +  (5x-7x^2)(5x-64) "  =

             =(5-14x)(5x-64)  +  (5x-7x^2)*5  =  25x - 70x^2 - 320 +896 + 25x   -  35x^2    = 

             =   -105x^2    +   50x    +   576